Prevalence and molecular characterization of multidrug-resistant staphylococcus species in a healthcare setting - Anyiam, Ifeoma Vivian; Uhegwu, Chijioke Christopher (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
Infection control within healthcare settings is a matter of great importance, as the emergence and spread of multidrug-resistant bacteria pose a significant threat to patient and healthcare workers’ safety. Staphylococcus species are notorious for their ability to develop resistance to multiple antibiotics, making them formidable nosocomial pathogens. Hence, this study was carried out to investigate the prevalence and molecular characteristics of multidrug-resistant Staphylococcus species in a healthcare environment. A total of 80 skin swab specimens were collected from different healthcare workers across different units at Federal Medical Centre, Yenagoa, and were analyzed by culture, gram staining, and biochemical tests, after which 27 isolates were obtained. The Staphylococcus species isolated include Staphylococcus epidermidis 13(48.2%), Staphylococcus aureus 12(44.4%), and Staphylococcus scuri 2(7.4%). Antibiotic susceptibility test revealed that the isolated Staphylococcus species were most resistant to cefotaxime, ceftriaxone, cefexime, imipenem/cilastatin, and cefuroxime, and most sensitive to amoxicillin-clavulanate, levofloxacin, ofloxacin, erythromycin, gentamycin, and azithromycin. There was a significant difference (p ≤ 0.05) in the antibiotic susceptibility profile of the isolated Staphylococcus species. Phylogenetic analysis using 16s rRNA sequences identified Staphylococcus scuri. Biofilm formation analysis indicated that Staphylococcus scuri and one strain of Staphylococcus epidermidis were biofilm producers. Plasmid profiling through gel electrophoresis indicated the presence of a plasmid molecular weight above 23130bp, suggesting the possibility of horizontal transmission of resistance genes. Plasmid curing of multidrug-resistant isolates resulted in improved antibiotic susceptibility. Continuous surveillance and molecular characterization of multi-drug resistant Staphylococcus species are necessary to mitigate the spread of these resilient pathogens.